Oligosaccharides from palm kernel cake enhances adherence inhibition and intracellular clearance of Salmonella enterica serovar Enteritidis in vitro - Foo, Rui Qing; Jahromi, Mohammad Faseleh; Chen, Wei Li; Ahmad, Syahida; Lai, Kok Song; Idrus, Zulkifli; Liang, Juan Boo (MDPI, 2020)
Salmonella enterica serovar (ser.) Enteritidis (S. Enteritidis) is a foodborne pathogen often associated with contaminated poultry products. This study evaluated the anti-adherence and intracellular clearance capability of oligosaccharides extracted from palm kernel cake (PKC), a by-product of the palm oil industry, and compared its efficacy with commercial prebiotics— fructooligosaccharide (FOS) and mannanoligosaccharide (MOS)—against S. Enteritidis in vitro. Based on the degree of polymerization (DP), PKC oligosaccharides were further divided into ‘Small’ (DP ≤ 6) and ‘Big’ (DP > 6) fractions. Results showed that the Small and Big PKC fractions were able to reduce (p < 0.05) S. Enteritidis adherence to Cancer coli-2 (Caco-2) cells at 0.1 mg/ mL while MOS and FOS showed significant reduction at 1.0 mg/mL and 10.0 mg/mL, respectively. In terms of S. Enteritidis clearance, oligosaccharide-treated macrophages showed better S. Enteritidis clearance over time at 50 µg/mL for Small, Big and MOS, while FOS required a concentration of 500 µg/mL for a similar effect. This data highlights that oligosaccharides from PKC, particularly those of lower DP, were more effective than MOS and FOS at reducing S. Enteritidis adherence and enhancing S. Enteritidis clearance in a cell culture model.